Nephroprotective Effect of Cilastatin against Gentamicin-Induced Renal Injury In Vitro and In Vivo without Altering Its Bactericidal Efficiency - Juan Carlos Jado (Antioxidants, 2020)
Gentamicin is a used antibiotic that causes nephrotoxicity in 10–20% of treatment periods, which limits its use considerably. Our results have shown that cilastatin may be a promising therapeutic alternative in toxin-induced acute kidney injury (AKI). Here, we investigated its potential use as a nephroprotector against gentamicin-induced AKI in vitro and in vivo. Porcine renal cells and rats were treated with gentamicin and/or cilastatin. In vivo nephrotoxicity was analyzed by measuring biochemical markers and renal morphology. Different apoptotic, oxidative and inflammatory parameters were studied at cellular and systemic levels. Megalin, mainly responsible for the entry of gentamicin into the cells, was also analyzed. Results show that cilastatin protects cells from gentamicin-induced AKI. Cilastatin decreased creatinine, BUN, kidney injury molecule-1 (KIM-1) and severe morphological changes previously increased by gentamicin in rats. The interference of cilastatin with lipid rafts cycling leads to decreased expression of megalin, and therefore gentamicin uptake and myeloid bodies, resulting in a decrease of apoptotic, oxidative and inflammatory events. Moreover, cilastatin did not prevent bacterial death by gentamicin. Cilastatin reduced gentamicin-induced AKI by preventing key steps in the amplification of the damage, which is associated to the disruption of megalin-gentamicin endocytosis. Therefore, cilastatin might represent a novel therapeutic tool in the prevention and treatment of gentamicin-induced AKI in the clinical setting.